The Role Of The Village Consultative Body In The Formulation Of Village Regulations - Rena Delya Citra; Louise Theresia; Ahmad setiawan (Kertha Patrika, 2026)
This study aims to examine and analyze the role of the Village Consultative Body (Badan Permusyawaratan Desa/BPD) in the formulation of Village Regulations (Peraturan Desa) in Simpang Naneng Village, Karusen Janang District, East Barito Regency. The BPD holds a strategic position as a representative institution that accommodates and channels the aspirations of the community, while also participating in the formulation of village policies together with the village government. This research employs a qualitative descriptive method, with data collected through interviews, observations, and documentation. The findings reveal that the BPD of Simpang Naneng Village has played an active role, particularly in the stages of planning and deliberation of village regulations. However, several obstacles remain, such as the limited understanding of BPD members regarding legal drafting procedures, inadequate human resource capacity, and weak coordination with the village government. These challenges often hinder the effectiveness and inclusiveness of policy-making at the village level. Despite these limitations, the involvement of BPD contributes significantly to promoting democratic governance and ensuring that community needs are reflected in village regulations. The study concludes that strengthening the capacity of BPD members, enhancing cooperation with the village government, and improving community participation are essential steps to create transparent, accountable, and participatory governance at the village level.
Keywords: Village Consultative Body; Village Regulation; Community Participation; Village Governance; Policy Formulation.